Prevalence and risk factors for cardiac iron overload and cardiovascular complications among patients with thalassemia in Northern Thailand - Tantiworawit A. (2017)
© 2017, SEAMEO TROPMED Network. All Rights Reserved. Cardiovascular complications are the most common cause of death among thalassemia patients in Thailand. In this study, we evaluated the prevalence of cardiac iron overload, cardiovascular complications and the associated risk factors. The information obtained will serve as a guidance for surveillance, prevention and early treatment of the complications. We conducted a cross sectional study of Thai patients with thalassemia attending Chiang Mai University Hospital, Thailand. Cardiac T2* magnetic resonance imaging (CMR T2*) was used to evaluate the myocardial iron deposition and echocardiography was used to evaluate the cardiac function and to identify pulmonary hypertension. Ninety-one patients were included in the study; 64% females with a median age of 31 (16-75) years. Of the total study subjects, 49% had homozygous β thalassemia, 32% had β thalassemia/Hb E disease, and 19% had Hb H disease. Half the participants were transfusion-dependent and 84% had received iron chelation. The CMR T2* showed cardiac iron overload in 10 patients (11%). The maximum ferritin level in the previous 3 years was higher among the patients with cardiac iron overload (6,310 ng/ml) than among the patients without cardiac iron overload (3,352 ng/ml) (p=0.001). Twenty-one patients (23%) had cardiovascular complications. Cardiomyopathy was seen in 8% of patients [17% in patients with transfusion-dependent thalassemia (TDT) and none in patients with non-transfusion-dependent thalassemia (NTDT)] and pulmonary hypertension in 15% of patients (14% in patients with TDT and 16% in patients with NTDT). TDT and cardiac iron overload were significantly associated with cardiomyopathy. No risk factors were found to be significantly associated with pulmonary hypertension. In summary, cardiac iron overload and cardiomyopathy are important complications in TDT while pulmonary hypertension is seen in both TDT and NTDT. Iron chelation and monitoring of serum ferritin level will prevent cardiac iron overload and cardiomyopathy. Interval monitoring with echocardiography will help with early identification of the cardiac complications.